Nauczanie dzieci języków obcych w kontekście akwizycji pierwszego języka - Garncarek, Piotr (Postscriptum Polonistyczne, 2020)
The article discusses the issues concerning native language acquisition and its influence on learning foreign languages. The article author presents theories defining the strategies of native language acquisition as well as their biological, social and communicative bases. He also discusses the difference between first and second language acquisition. Being aware of such a difference enables a teacher to design an efficient study programme.